Tindak Tutur Performatif dalam Cerita Anak Jepang: Kajian Pragmatik - Iriantini, Sri (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
A communication is formed from various utterances consisting of various meaningful sentences. When communicating, a person says an utterance that pragmatically will bring meaning not only lexically, grammatically, but also contextually. The utterance that is expressed contains a certain intention of the speaker so that it is called a speech act, and a speech act that performs the speaker's intention is called a performative speech act. Performative speech acts can be marked by the presence of performative verbs explicitly, or not marked by performative verbs, but in context can be understood as performative speech implicitly. The type of performative verb used is also adjusted to the purpose of the speech, which can be declarative, representative, directive, expressive, or commissive. This research discusses this, with data taken from Japanese children's stories, to find out the types of performative speech that often appear in Japanese children's stories, and the types of performative verbs that are often used. The theory used in this research is pragmatics theory, with descriptive qualitative research method, literature study research technique, which then the data is studied with distributional method and element sorting technique. The results of this study show that implicit performative speech acts are more common than explicit performative speech acts in Japanese children's stories. Furthermore, the implicit performative.